2020
DOI: 10.1097/ccm.0000000000004704
|View full text |Cite
|
Sign up to set email alerts
|

Ventilator-Weaning Pathway Associated With Decreased Ventilator Days in Pediatric Acute Respiratory Distress Syndrome*

Abstract: Objectives: There is limited evidence on the impact of protocolized ventilator weaning in pediatric acute respiratory distress syndrome, despite utilization in clinical trials and clinical care. We aimed to determine whether protocolized ventilator weaning shortens mechanical ventilation duration and PICU length of stay in pediatric acute respiratory distress syndrome survivors. Design: Secondary analysis of a prospective pediatric acute respiratory dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Use of systematic standardized ERT may improve outcomes (61). Foronda et al (62) found in a randomized controlled trial (RCT) that daily ERT in children reduced the duration of MV.…”
Section: Resultsmentioning
confidence: 99%
“…Use of systematic standardized ERT may improve outcomes (61). Foronda et al (62) found in a randomized controlled trial (RCT) that daily ERT in children reduced the duration of MV.…”
Section: Resultsmentioning
confidence: 99%
“…Multivariable regression was used to compare mortality and posttransfer LOS in days among cases with and without MOID with a priori defined confounders of age category, originating service, deterioration category, and pretransfer LOS, 3 which have been associated with risk of mortality in ET and were hypothesized to impact the diagnostic process in deteriorating patients. 2,24 Mortality was modeled with logistic regression. We modeled posttransfer LOS with a generalized linear model with log link, gamma family, and robust variance estimates to account for the right-skewed distribution.…”
Section: Discussionmentioning
confidence: 99%
“…We compared ET cases with and without MOID using descriptive statistics, including Fisher's exact test for categorical variables. Multivariable regression was used to compare mortality and posttransfer LOS in days among cases with and without MOID with a priori defined confounders of age category, originating service, deterioration category, and pretransfer LOS, 3 which have been associated with risk of mortality in ET and were hypothesized to impact the diagnostic process in deteriorating patients 2,24 . Mortality was modeled with logistic regression.…”
Section: Methodsmentioning
confidence: 99%
“…Recent single-center studies assessing physician-directed versus protocolized weaning of mechanically ventilated pediatric patients have had promising results in demonstrating feasibility and safety 23,24 and shortened time to spontaneous breathing but have had conflicting results on time to extubation. [25][26][27][28][29][30][31] In a secondary analysis of infants with lower respiratory tract disease, the SBT demonstrated a high positive predictive value for extubation success. 32 However, the authors of this study found that 34% of patients who passed their first SBT were not extubated on that day, with physician preference (26%) cited as the most common reason.…”
Section: Introductionmentioning
confidence: 97%